All about seeds - Berger, Melvin; DiVito, Anna (New York : Scholastic, 1992)
Identifies various kinds of seeds, what they need to grow, how they scatter, and the role seeds play in feeding the world. Includes eight simple experiments.
Keywords: Germination -- Juvenile literature; Germination -- Experiments -- Juvenile literature; Seeds -- Juvenile literature; Seeds -- Experiments -- Juvenile literature; Experiments; Seeds -- Experiments